Approximation of locally integrable functions on the real line - Stepanets, O. I.; Wang, Kunyang; Zhang, Xirong (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We introduce the notion of generalized \(ψ \) -derivatives for functions locally integrable on the real axis and investigate problems of approximation of the classes of functions determined by these derivatives with the use of entire functions of exponential type.